2009
DOI: 10.1093/cercor/bhp196
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Temporospatial Interhemispheric Interactions in the Human Primary and Premotor Cortex during Movement Preparation

Abstract: The preparation of a voluntary unimanual action requires sequential processing in bihemispheric motor areas. In both animals and humans, activity in the dorsal premotor cortex (PMd) ipsilateral to the moving hand has been demonstrated to precede ipsilateral primary motor cortex (M1) activity. We investigated with double-pulse transcranial magnetic stimulation how right-hemispheric motor areas (rM1, rPMd) modulate left M1 (lM1) during the preparatory period of a finger movement with the dominant right hand. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
53
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 79 publications
15
53
3
Order By: Relevance
“…We found that ϳ90 ms before movement onset, IHI decreases during selfpaced and ballistic index finger and elbow movements compared to rest. This is in agreement with previous evidence showing that during the preparatory phase of ballistic movements IHI targeting the ipsilateral limb decreases compared to rest (Murase et al, 2004;Duque et al, 2005;Liuzzi et al, 2010). Previous studies demonstrated that interhemispheric sharing during a motor task modulates the speed of upcoming movements (Guiard and Requin, 1977).…”
Section: Transcallosal Inhibition In the Preparatory Phase Of Ipsilatsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that ϳ90 ms before movement onset, IHI decreases during selfpaced and ballistic index finger and elbow movements compared to rest. This is in agreement with previous evidence showing that during the preparatory phase of ballistic movements IHI targeting the ipsilateral limb decreases compared to rest (Murase et al, 2004;Duque et al, 2005;Liuzzi et al, 2010). Previous studies demonstrated that interhemispheric sharing during a motor task modulates the speed of upcoming movements (Guiard and Requin, 1977).…”
Section: Transcallosal Inhibition In the Preparatory Phase Of Ipsilatsupporting
confidence: 92%
“…Indeed, transcallosal inhibition progressively decreases during the preparatory phase of fast movements compared to rest (Murase et al, 2004;Duque et al, 2005;Liuzzi et al, 2010). The increases in movement speed also results in increments in electromyographic (EMG) activity during movement execution.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies using TMS (and combined fMRI) in humans suggest a functional influence of (left) PMd upon the opposite PMd (and M1) that is strongly state dependent: varying in accordance with the nature of the task being performed by the ipsilateral limb (Bestmann et al, 2008). During movement preparation, there is a corresponding influence of (right) PMd on opposite M1, which precedes interhemispheric interactions between the homologous primary motor areas (Liuzzi et al, 2010). It is possible, therefore, that the state (i.e., vision)-dependent modulation of crossed facilitation observed in the present study was mediated via differential PMd control of interneuronal (i.e., inhibitory) circuitry within left and right M1.…”
Section: Discussionmentioning
confidence: 99%
“…This neural structure, possibly aided by the basal ganglia (Stocco, Lebiere, & Anderson, 2010), organizes activity in regional networks by adjusting the functional connectivity across multiple cortical regions (Elsinger, Harrington, & Rao, 2006;Gelnar, Krauss, Sheehe, Szeverenyi, & Apkarian, 1999;Liuzzi et al, 2010;Roland, Larsen, Lassen, & Skinhoj, 1980). Furthermore, it also controls sensory input via the thalamus (Brunia, 1999).…”
Section: Neural Underpinningsmentioning
confidence: 99%